Several Factors Affecting the Work Stress of Nurses at Dr. Hadrianus Sinaga Hospital, Samosir Regency in 2023 - Sri Agustina; Toni Wandra; Henny Syapitri (SEAN Institute, 2023)
Work stress in nurses, such as burnout, anxiety, and depression, can interfere with the performance of nurses due to reduced physical and cognitive abilities due to mental health disorders. The research objective was to determine the factors that influence the work stress of nurses at Dr. Hadrianus Sinaga, Samosir Regency, 2023. The research design used a cross-sectional study. The research population is all nurses who work in RSUD, Dr. Hadrianus Sinaga, Samosir Regency, consisting of 144 people, with the total sample being the total population. Data analysis using univariate analysis, bivariate, and multivariate analysis. The results showed that the individual factors, namely age, gender, education level, status, and length of work, did not show a significant relationship (p> 0.05). The work factors, which include workload and work conflict, also did not show a significant relationship (p> 0.05). Likewise, the supporting factors did not show a significant relationship (p> 0.05). Although it did not show a significant relationship, the proportion of work stress was higher for nurses who received less support from the hospital than nurses who received good support. For this reason, the hospital continues to support nurses, including certificates of appreciation or incentives/medical services according to the hospital's capabilities.